Posicionamento estratégico, integração vertical e desempenho econômico-financeiro em operadoras de planos de saúde - Nascimento, Alan Junior do (Universidade do Vale do Rio dos Sinos, 2021)
The study evaluates the relationship between the strategic positioning and the financial performance of health insurance companies and evaluates the moderating effect of vertical integration in this relationship. For this purpose, information was collected through a questionnaire from 239 companies. Confirmatory factor analyzes, multiple linear regressions, and mean difference tests were performed. The differentiation strategy, in its pure form, was found in only 12.55% of the sample; costs leadership, at 15.15%; hybrid in 47.18%; and 25.1% were stuck in the middle. The results showed no statistically significant differences in companies' financial performance that adopt cost leadership or differentiation individually, as well as the hybrid strategy. Companies stuck in the middle performed less well than companies that adopted the hybrid strategy and pure cost leadership or differentiation strategies. Verticalized companies performed better than non-verticalized ones. However, the interaction of vertical integration with strategy variables does not moderate the positioning and performance relationship. It is inferred that the hybrid strategy's success results from a change in the competition pattern if compared to the context in which Porter developed the proposition. To the list of research on strategy, the results add empirical contributions to the strategic positioning adopted by health plan operators and their competition patterns. The study also expands the literature on the hybrid strategy while collaborating with studies that have identified positive results linked to it. Based on the results, managers will be able to direct resources to practices that have the greatest contribution to achieving and sustaining competitive advantage in the long run.
Keywords: Estratégias genéricas; Integração vertical; Desempenho; Operadoras de planos de saúde; Generic strategies; Vertical integration; Performance; Health insurance; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis